2018
DOI: 10.1111/ppl.12790
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hydraulic conductivity loss from relative water loss: new insights into water storage of tree stems and branches

Abstract: More frequently occurring, drought waves call for a deeper understanding of tree hydraulics and fast and easily applicable methods to measure drought stress. The aim of this study was to establish empirical relationships between the percent loss of hydraulic conductivity (PLC) and the relative water loss (RWL) in woody stem axes with different P , i.e. the water potential (Ψ) that causes 50% conductivity loss. Branches and saplings of temperate conifer (Picea abies, Larix decidua) and angiosperm species (Acer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…In some cases, however, trunks were reported to be more vulnerable than branches (e.g. Johnson et al, 2016;Rosner et al, 2018), and other studies found similar vulnerabilities across organs (e.g. Choat et al, 2005;Hao et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…In some cases, however, trunks were reported to be more vulnerable than branches (e.g. Johnson et al, 2016;Rosner et al, 2018), and other studies found similar vulnerabilities across organs (e.g. Choat et al, 2005;Hao et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…The phloem is the other transport tissue which brings carbohydrates downward in the plant from the leaf source to its sinks (Sala et al 2010, Nikinmaa et al 2013, Rathgeber et al 2016, Castagneri et al 2017, Ziaco et al 2018. Both xylem and phloem interact through changes in osmotic pressure and water potential, regulating the water and carbohydrate transports in the plant (Botha 2005, Cochard et al 2009, Holtta et al 2009, Rosner et al 2018, Sevanto et al 2018, as well as turgor. They therefore interact to modify Tr and GPP (Nikinmaa et al 2013, Konrad et al 2018).…”
Section: Soil Moisture Effects On Water-carbon Couplingmentioning
confidence: 99%
“…Screening tools should be economical, require little labor, not be time-consuming, easy in application and -last but not least -applicable to conifers worldwide. Recently, Rosner et al (2019) presented an approach where hydraulic conductivity loss of angiosperm and conifer sapwood could be predicted from simple water loss measurements. The empirical predicting models in this preceding study were however species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…The RWL method allows the comparison of the samples differing in total water volume and wood density (Domec and Gartner 2001). Rosner et al (2019) defined an additional capacitance parameter, the RWL at P 50 , i.e., the RWL that results from 50% conductivity loss. RWL at P 50 varies widely across angiosperm and conifer species and is negatively related to wood density, as found for other capacitance traits as well (Pratt et al 2007;Scholz et al 2007;McCulloh et al 2014;Trifilò et al 2015;Savi et al 2017;Pratt and Jacobsen 2017).…”
Section: Introductionmentioning
confidence: 99%